Vibrio Cholerae O1 Ogawa bacteremia with Extraintestinal manifestation - Faisal, Ummu Salamah; Zainulabid, Ummu Afeera; Kori, Najma; Periyasamy, Petrick; Khaithir, Tzar Mohd Nizam (2022)
O1 Ogawa Vibrio cholerae is rarely reported causing extraintestinal manifestation. Here, we report a case of O1 Ogawa Vibrio cholerae bacteremia with bullous cellulitis of the left leg. The patient acquired the infection through a small skin prick on her leg from contaminated soil that served as an environmental reservoir for Vibrio cholerae.